Assembly of multiprotein complexes that control genome function - Dinant, Christoffel (The Rockefeller University Press, 2009)
Live-cell imaging studies aided by mathematical modeling have provided unprecedented insight into assembly mechanisms of multiprotein complexes that control genome function. Such studies have unveiled emerging properties of chromatin-associated systems involved in DNA repair and transcription.